Prevalence of bacterial Uropathogens in patients with acute, recurrent and chronic urinary tract infection in Kirkuk city, Iraq - Mohammed, Fatma Mustafa; Saleh, Mahmood K. (Edelweiss Applied Science and Technology, 2024)
Urinary tract infections (UTIs) are one of the most common types of infections. They place a huge burden on health systems worldwide. Urinary tract infections (UTIs) are one of the most common bacterial infections and are a major problem worldwide. The most important problem is recurrence of infection and may develop into chronic cases. This study aimed to evaluate the pathogens and their types in acute, recurrent and chronic urinary tract infections in Kirkuk Governorate. 151 urine samples were collected from patients with urinary tract infections who visited private clinics in Kirkuk Governorate. They were diagnosed by a urologist for the period from December 2022 to October 2023. The ages of the patients ranged from 21-76 years. Microscopic examination, laboratory tests, culture and isolation of pathogens were performed and the diagnosis was confirmed using the Vitek device to diagnose bacterial isolates with a high degree of accuracy after confirming them by initial biochemical tests. In the current study, the number of male patients with urinary tract infections was 62, representing 41.1%, while the number of female patients was 89, representing 58.9%. The case was diagnosed as acute, recurrent or chronic. The results of the current study showed that the number of samples for patients with acute urinary tract infections was 91 samples, representing 60.3%. The number of males was 37, representing 40.7%, and the number of females was 54, representing 59.3%. As for the cases of patients with recurrent urinary tract infections, their number was 23, representing 42.6% of males, while the number of females was 31, representing 57.4%. As for the chronic cases, the number of males was 2, representing 33.3%, while the number of females was 4, representing 66.7%. After the cases of the patients to be studied were diagnosed, the diagnostic results showed the difference in the types of bacteria isolated, and it was found that they were for. E coli, where their number was 76 and their percentage was 50.4%, while Klebsiella pneumonia was also among the most common isolates in our study, where their number was 23 and their percentage was 15.3%, and these two isolates were the most common in all the clinical cases that were studied. The results of this work showed that the two most common isolates in patients with acute, recurrent and chronic urinary tract infections are Klebsiella. Pneumonia and E coli.